PENENTUAN KECEPATAN PEMOTONGAN EFEKTIF BERDASARKAN NILAI KEKASARAN PERMUKAAN MATERIAL AA-7075 PADA PROSES FACE MILLING - Sobron Y. Lubis; Rosehan Rosehan; Musa Law (Jurnal Ilmiah Teknik Mesin POROS, 2021)
During face milling machining, several machining parameters such as feed rate and cuttingspeed determine the surface quality of the workpiece produced by the process. The selection of the rightparameters will lead to the surface quality as planned. Therefore, to improve machining effectiveness, amethod is needed to determine the appropriate machining parameters to produce the desired surfacequality. This research was conducted using a milling machine, five variations of cutting speed and fivevariations of feed rate were used to cut the workpiece aluminum alloy 7075. After machining, the surfaceroughness was measured using a surface test. The surface roughness value is then substituted into thefeed rate equation and effective cutting speed. By finding effective cutting parameters, the machiningprocess will be more efficient and effective without using unnecessary resources. From the results of thestudy note that the development equation to determine the feed rate based on the value of surfaceroughness is ???? = 0,6????√???? ????????0.443mm/tooth. Development equation to determine the effective cutting speedbased on Surface roughness value is ???????? = 3.0686????????0.124 mm/min